La Liga Filipina Rizal and institutional change. - Jandoc, Karl Robert L. (Philippine Review of Economics, 2011)
A long-standing tradition in economics contends that “institutions matter" for long-run growth. Whether defined as “rules of the game” or a “system of social factors,” institutions ultimately affect the cost of exchange and production that, in turn, influences economic performance. This paper shows that Rizal, by establishing La Liga Filipina, endeavored to create the conditions toward institutional change. It shows that through the Liga’s aims—(a) to unite the whole archipelago;(b) mutual protection in case of trouble and need; (c) defense against every violence and injustice; (d) development of education, agriculture, and commerce; and (e) study and implementation of reforms—Rizal sought to subvert the most important antidevelopment institutions of his day.